The problem of the book of Jonah - Aalders, Gerhard Charles, 1880-; Tyndale Fellowship for Biblical Research (London, UK Tyndale, 1948)
Includes bibliographical references.
Lecture delivered in Tyndale House, Cambridge on July 9th, 1948 at a meeting convened by the Tyndale Fellowship for Biblical Research.
Keywords: Bible. O.T. Jonah -- criticism, interpretation, etc